The students’ critical thinking ability through problem posing learning model viewed from the students’ curiosity - Permanawati, Fitra Inda; Agoestanto, Arief; Kurniasih, Ary Woro (Department of Mathematics, Universitas Negeri Semarang, 2018)
Critical thinking is an embodiment of high level thinking. The purposes of this research were to know that the critical thinking ability of class VIII SMP Negeri 1 Wangon on Problem Posing passes the learning completeness grade, the critical thinking ability of class VIII SMP Negeri 1 Wangon on Problem Posing is better than Direct Instruction, and to describe the students’ critical thinking ability through Problem Posing seen from the students’ curiosity. The results showed that: 1) critical thinking ability of class VIII SMP Negeri 1 Wangon on Problem Posing pass the learning completeness grade; 2) critical thinking ability of class VIII SMP Negeri 1 Wangon on Problem Posing is better than Direct Instruction; 3) subject with high curiosity are able to accomplish 6 indikators, while the subject with medium curiosity are able to accomplish 5 indikators, and subject with low curiosity are able to accomplish 3 indikators.